2016
DOI: 10.1039/c6tb02268e
|View full text |Cite
|
Sign up to set email alerts
|

Protease-sensitive atelocollagen hydrogels promote healing in a diabetic wound model

Abstract: Protease-sensitive atelocollagen hydrogels were chemically designed to promote accelerated wound healingin vivocompared to a dressing gold standard.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 61 publications
4
32
0
Order By: Relevance
“…Atelocollagen “as received” was the thickest collagen sample and revealed the highest swelling degree and temperature dependency of all collagen samples, with a swelling degree at RT almost twice as high as at 37 °C. Large swelling ratios of Atelocollagen have been reported previously [ 43 , 44 ]. As revealed by light microscopy and SEM, Atelocollagen possessed much larger cavities than Collagen Solutions and Viscofan samples ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 60%
“…Atelocollagen “as received” was the thickest collagen sample and revealed the highest swelling degree and temperature dependency of all collagen samples, with a swelling degree at RT almost twice as high as at 37 °C. Large swelling ratios of Atelocollagen have been reported previously [ 43 , 44 ]. As revealed by light microscopy and SEM, Atelocollagen possessed much larger cavities than Collagen Solutions and Viscofan samples ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 60%
“…The modulation of collagen secretion by fibroblasts in hydrogels for understanding mechanical cues that can alter wound healing using non‐linear optics is a relatively new approach for tissue engineering. Collagen gels have been studied in the past for their efficacy in hastening the wound healing process toward granular tissue formation . The structure and orientation of collagen fibers have been studied for their influence on cell‐mediated migration, which could play an important role in the remodeling of the wound site .…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that dopamine barely releases from the PLGA fibers. The release of drug is often accompanied by material degradation [24]. However, the situation was different in the polydopamine-assisted system.…”
Section: Kinetics Of Absorption and Releasementioning
confidence: 99%